MORPHOLOGICAL DIVERSITY ON FRUIT CHARACTERISTICS AMONG SOME SELECTED MULBERRY GENOTYPES FROM TURKEY - K. U. Yilmaz; Y. Zengin; S. Ercisli; M. N. Demirtas; T. Kan; A. R. Nazli (Journal of Animal and Plant Sciences, 2012)
Turkey has important mulberry genetic resources. In contrast to the other mulberry producing countries, in Turkey mulberry tree is used only for fruit production not for sericulture purposes. Some selected morphological fruit characteristics such as seed formation, fruit weight, SSC (Soluble solid content), titratable acidity, juice yield and pH of 34 selected mulberry genotypes found together in an ex-situ collection parcel in Malatya Fruit Research Institute in Turkey were investigated. The collection parcel has been established in 1996 year with 3x5 m row spacing. The morphological fruit characteristics are represented of 3 years average data (2006-2008). The results showed that there were big differences among genotypes in terms of most of the fruit characteristics. Fruit weight varied from 0.66 (Istanbul dutu 2) to 3.07 (Gumushaci beyaz); SSC varied from 17.33% (Erzincan karadut 16) to 30.67% (Lokum dut); titratable acidity varied from 0.06% (Angut 9) to 1.62% (Gumushaci karadut 8) and pH varied from 2.19 (Kemaliye karadut 9) to 5.86 (Mersin mor dut), respectively.
Keywords: Mulberry; biodiversity; plant science; fruit characteristics.